HMAP, World Hepatitis Day and the bigger health systems picture. Issue 1 (December 2016) - Lazarus, Jeffrey; Safreed-Harmon, Kelly; Maticic, Mojca
Abstract World Hepatitis Day 2016 marks one year sinceHepatology, Medicine and Policy (HMAP ) began accepting submissions. There have been many major developments in the fight against hepatitis B virus (HBV) and hepatitis C virus (HCV) infections during this time, but there is no guarantee that the global community's interest in these diseases will endure. Situating efforts to eliminate HBV and HCV within the movement to strengthen health systems is the key to ensuring that current momentum is sustained. Because of the very nature of viral hepatitis, an effective response requires the integration of many seemingly disparate components of health systems. Everyone working to end HBV and HCV epidemics thus has a vested interest in health systems strengthening. Furthermore, it is important for strategic purposes to look beyond what hepatitis stakeholders need from health systems, and to ask how the global response to HBV and HCV can help foster health systems innovations and put patient-centered care first. Addressing this question explicitly is central to ensuring that the long-term relevance of the viral hepatitis movement is recognized by diverse health and development actors.